2021
DOI: 10.3390/nu13051459
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exercise, Diet, and Cytokines in Preventing Obesity and Improving Adipose Tissue

Abstract: The prevalence of obesity continues to rise worldwide despite evidence-based public health recommendations. The promise to adopt a healthy lifestyle is increasingly important for tackling this global epidemic. Calorie restriction or regular exercise or a combination of the two is accepted as an effective strategy in preventing or treating obesity. Furthermore, the benefits conferred by regular exercise to overcome obesity are attributed not only to reduced adiposity or reduced levels of circulating lipids but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 345 publications
0
38
0
Order By: Relevance
“…VO 2max [3,156,160,161]. In these studies, the first exercise sessions were generally an exercise that depleted muscle-glycogen stores, and the second exercise session was performed with low muscle-glycogen stores that potentiated the exercise-induced increase in genes linked to mitochondrial biogenesis and metabolism [156,160,161,[163][164][165].…”
Section: Adaptations To Once-or Twice-daily Hiitmentioning
confidence: 99%
See 2 more Smart Citations
“…VO 2max [3,156,160,161]. In these studies, the first exercise sessions were generally an exercise that depleted muscle-glycogen stores, and the second exercise session was performed with low muscle-glycogen stores that potentiated the exercise-induced increase in genes linked to mitochondrial biogenesis and metabolism [156,160,161,[163][164][165].…”
Section: Adaptations To Once-or Twice-daily Hiitmentioning
confidence: 99%
“…These studies reported twice-daily exercise sessions (wherein the second session was commenced with reduced muscle glycogen stores) improved energy metabolism and induced skeletal-muscle cell-signaling pathways regulating mitochondrial and substrate metabolism [ 159 , 160 , 161 , 162 ]. Of the limited studies available, the twice-a-day approach has also been shown to be more effective than “once-daily” exercise for inducing adaptations related to substrate oxidation during submaximal exercise, endurance capacity, and O 2max [ 3 , 156 , 160 , 161 ]. In these studies, the first exercise sessions were generally an exercise that depleted muscle-glycogen stores, and the second exercise session was performed with low muscle-glycogen stores that potentiated the exercise-induced increase in genes linked to mitochondrial biogenesis and metabolism [ 156 , 160 , 161 , 163 , 164 , 165 ].…”
Section: Physiological Mechanisms Associated With Hiit-induced Adaptationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, abnormalities in myokine secretion and function may have a direct influence on the worsening of insulin resistance. However, the mechanism by which myokines affect insulin resistance has not been fully elucidated [ 87 , 92 , 93 , 94 ].…”
Section: Intermittent Hypoxia and Cytokinesmentioning
confidence: 99%
“…Exercise increases decorin (myokine associated with muscle fiber proliferation) and IGF-1, which have muscle-protein-synthesispromoting effects, and conversely decreases myostatin, which has muscle-protein-synthesisinhibiting effects [95]. A continuous exercise habit increases brown adipose tissue [98]. Brown adipose tissue also regulates myostatin secretion and is involved in the regulation of skeletal muscle mass and skeletal muscle function [99].…”
Section: Interventions For Met-s-associated Sarcopeniamentioning
confidence: 99%